Police leaders make poor change agents: leadership practice in the face of a major organisational reform - Haake, Ulrika (Policing and society, 2017)
The present article examines expectations on police leaders during major organisational change pressures. Based on policy analysis and interviews with 28 police leaders, the paper seeks to answer the following question: How do police leaders’ accounts of leadership practice relate to expectations from higher ranks (above), subordinates (below) and police policies concerning leadership? The results of the paper indicate that police leaders are squeezed into a position between demands from above (top management) and demands from below (lower organisational tiers). Some of the perceived expectations and practiced leadership actions are also gendered. For example, women feel the need to prove their credibility as leaders and to act in both a caring and daring manner, something that is not evident for male police leaders. Furthermore, the material indicates a considerable mismatch between the different sets of demands expressed in interviews and expectations regarding leadership expressed in police policy discourse, wherein core values and leadership criteria are articulated. In conclusion, the findings indicate a discrepancy between official rhetoric and practice, where the leadership constructed at a policy level deviates from leadership constructed in practice. This discrepancy is argued to represent an effective barrier for change initiatives, and hence the idea that police leaders will be able to function as agents of change promoting organisational reform is highly uncertain.